Molecular Biology Techniques An Intensive Laboratory Course - Ream, Walt Field, Katharine G (Academic Press, 1999)
This manual is designed as an intensive introduction to the various tools of molecular biology. It introduces all the basic methods of molecular biology including cloning, PCR, Southern (DNA) blotting, Northern (RNA) blotting, Western blotting, DNA sequencing, oligo-directed mutagenesis, and protein expression. Key Features * Provides well-tested experimental protocols for each technique * Lists the reagents and preparation of each experiment separately * Contains a complete schedule of experiments and the preparation required * Includes study questions at the end of each chapter.